Malaysian property industry: Challenges faced by practitioners in the adoption of green building concept - Chen, Wan Shi (2022)
It is without doubt that the green movement is constantly growing throughout recent years. Although the green building concept is a vital key to improve Malaysian’s standards, there is still a large gap in terms of people’s understanding and awareness on green building issues where Malaysia faces difficulty in implementing the green building concept. This is caused by the slow pace and hesitance to participate in it. Therefore, this research aims to evaluate on the most challenge faced by practitioners in the implementation of green building concept towards the Malaysian property industry. About 100 questionnaires are used to collect data and analysed using descriptive analysis and relative importance index. The results obtained shows that there were eight challenges and the lack of professional knowledge was the most difficult challenge faced by practitioners in the adoption of green building concept in the construction industry. Thus, practitioners are required to join more related events, training and seminars to gain more knowledge. Furthermore, the future researchers are encouraged to study on the knowledge required to be obtained by practitioners or even study specifically on only one practitioner or property type.